(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The physicochemical qualities of the effluent samples of three Wastewater sites (Sazidehra site, Raipura site and Nayapura site) and one control site (Akelgarh site) in Kota district of Rajasthan, India were evaluated from three slots of time in the year i.e., September, December and March using standard methods. The physicochemical parameters assessed included color, odor, pH, temperature, total dissolved solid (TDS), turbidity (NTU), Biological Oxygen Demand (BOD), Chemical oxygen demand (COD), dissolved oxygen (DO) and Heavy metals. The results of the evaluation were as follows: temperature (28 ºC-36ºC), COD (17-92mg/L), and turbidity (1.96-286 NTU), BOD (2-7mg/l), DO (1-7mg/l) and TDS (175-1890mg/l). The temperature, TDS, turbidity, COD, DO were not found to be in the recommended limits. Some of the parameters exceeded from their normal ranges and some found to be below the range that ensure the contaminants present in the water and considering the samples unhealthy for drinking and highly polluted. The Raipura site was found highly contaminated. The heavy metals were concentrated in the research area, which suggests that the river is severely polluted. Zinc (Zn) was found highly (267ppm) accumulated in the sewage water of Raipura site. We conclude that these sewage dumping areas of water sources are polluted to their respective receiving watersheds and threats to public and environmental health.